Double Outlet Right Ventricle With Right-Sided Aorta From the Left-Sided Morphologically Right Ventricle in the Setting of Discordant Atrioventricular Connections. Issue 4 (July 2020) - Talwar, Sachin; Anderson, Robert H.; Bhoje, Amolkumar; Crucean, Adrian; Gupta, Saurabh Kumar; Choudhary, Shiv Kumar; Airan, Balram
We describe the anatomic findings in a 2-year-old patient with double outlet right ventricle with right-sided aorta in the setting of usual atrial arrangement and discordant atrioventricular connections, making comparison with a specimen from the pathological archive of the Birmingham Children's Hospital in the United Kingdom having this rare combination of anatomic features. We discuss the challenges involved in diagnosis and management.